Polyurethane and graphene composite methane adsorption material and preparation method thereof
By incorporating graphene modified isocyanate into the polyurethane system, a composite methane adsorption material of polyurethane and graphene was prepared, which solved the limitations of the existing materials in adsorption performance, stability and mechanical properties, and achieved efficient and environmentally friendly methane adsorption effect.
Patent Information
- Application Number
- CN202411875971.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-15
AI Technical Summary
Existing methane adsorbent materials have limitations in adsorption performance, stability and regenerative properties, and it is difficult to meet the needs of efficient and environmentally friendly energy storage and utilization.
By incorporating graphene-modified isocyanate into the polyurethane system, the preparation process of accurately proportioning each component and optimizing the graphene-modified isocyanate, a composite methane adsorption material of polyurethane and graphene was prepared.
It significantly improves the methane adsorption capacity and mechanical properties of the material, ensures the durability and processing performance of the composite material, is suitable for diverse product needs, and shows broad application potential.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyurethane, and in particular relates to a polyurethane and graphene composite methane adsorption material and a preparation method thereof. Background Art
[0002] With the continuous growth of global energy demand and the increasing awareness of environmental protection, finding efficient and environmentally friendly ways to store and utilize energy has become an important direction of current scientific and technological research. Methane, as a clean energy, has broad application prospects in the energy field. However, the safety and efficiency issues in the storage and transportation of methane have always been the key factors restricting its widespread application. Therefore, it is particularly important to develop a methane adsorption material with high adsorption performance, good stability and safety.
[0003] Traditional methane adsorption materials mainly include activated carbon, molecular sieves, etc., but these materials have certain limitations in terms of adsorption performance, stability and regeneration. In recent years, graphene, as a new type of nanomaterial, has shown great application potential in the fields of energy, environmental protection, and materials science due to its unique two-dimensional structure and excellent physical and chemical properties. Graphene has an extremely high specific surface area and excellent electrical and thermal conductivity, which makes it an ideal choice for the preparation of high-performance methane adsorption materials.
[0004] At present, there have been studies on the composite of graphene and polymer to prepare composite materials with excellent performance. Among them, polyurethane, as a commonly used polymer material, has good processing performance and mechanical properties. Composite with graphene can further improve the overall performance of the material. However, how to evenly disperse graphene in the polyurethane matrix and give full play to its adsorption performance is a problem that needs to be solved in current research. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a polyurethane and graphene composite methane adsorption material. By accurately proportioning the components and optimizing the preparation process of graphene-modified isocyanate, the prepared composite material not only has excellent methane adsorption performance, but also exhibits good mechanical properties.
[0006] Another object of the present invention is to provide a method for preparing a polyurethane and graphene composite methane adsorption material, which has a simple process and is easy for industrial production.
[0007] The technical solution adopted by the present invention is as follows:
[0008] The polyurethane and graphene composite methane adsorption material comprises component A and component B in a mass ratio of 1:(1-1.2);
[0009] The A component includes the following raw materials in parts by weight:
[0010] Polyether polyol A: 50-60 parts;
[0011] Polyether polyol B: 30-40 parts;
[0012] Polyether polyol C: 5-10 parts;
[0013] Polyether polyol D: 5-10 parts;
[0014] Foam stabilizer: 3-5 parts;
[0015] Physical foaming agent: 13-16 parts;
[0016] Chemical foaming agent: 2-3 parts;
[0017] Composite catalyst: 9-12 parts;
[0018] The B component is graphene-modified isocyanate;
[0019] The functionality of the polyether polyol A is 4-6, and the hydroxyl value is 360-400 mgKOH / g;
[0020] The functionality of the polyether polyol B is 3.8-4.2, and the hydroxyl value is 360-400 mgKOH / g;
[0021] The functionality of the polyether polyol C is 4, and the hydroxyl value is 745-775 mgKOH / g;
[0022] The functionality of the polyether polyol D is 4, and the hydroxyl value is 350-380 mgKOH / g;
[0023] The preparation method of the graphene-modified isocyanate is as follows: adding graphene to N,N-dimethylformamide, then adding polyvinyl pyrrolidone, and ultrasonically obtaining a graphene dispersion; adding isocyanate and a tin catalyst to the graphene dispersion, heating the reaction, and filtering after the reaction is completed to obtain the graphene-modified isocyanate.
[0024] The viscosity of the polyether polyol A at 25°C is 6000-9000 mPa·s; the viscosity of the polyether polyol B at 25°C is 2000-3000 mPa·s; the viscosity of the polyether polyol C at 50°C is 1400-2400 mPa·s; and the viscosity of the polyether polyol D at 25°C is 8000-12000 mPa·s.
[0025] In the preparation method of the graphene-modified isocyanate, the isocyanate is polymethylene polyphenyl polyisocyanate, preferably PM200 produced by Wanhua Chemical Group Co., Ltd.; the tin catalyst is dibutyltin dilaurate; the amount of graphene added is 1-3wt.% of the total amount of isocyanate, the mass ratio of graphene to N,N-dimethylformamide is 1:(50-100), the amount of polyvinyl pyrrolidone added is 0.1-0.5wt.% of the total amount of graphene, and the amount of tin catalyst added is 0.1-0.5wt.% of the total amount of isocyanate.
[0026] The foam stabilizer is silicone oil, preferably H3565, purchased from Zhongshan Dongjun Chemical Co., Ltd.; UR5931, purchased from Jiangsu Aoshijia Materials Technology Co., Ltd.
[0027] The physical foaming agent is pentane, preferably n-pentane.
[0028] The chemical foaming agent is water.
[0029] The composite catalyst is a composite catalyst of PC-5, PC-8, BDMA, PC-41 and TMR-2, and the mass ratio thereof is (0.3-0.6):(5-7):(2-3):(0.5-2):0.5.
[0030] The polyether polyols A, B, C and D are R5118G, R6205, R403 and 4400T respectively, all of which are purchased from Shandong Yinuowei New Materials Co., Ltd.
[0031] The particle size of the graphene is 10-40 μm.
[0032] The preparation method of the polyurethane and graphene composite methane adsorption material comprises the following steps: putting polyether polyol A, polyether polyol B, polyether polyol C, polyether polyol D, a foam stabilizer, a composite catalyst and a chemical foaming agent into a reaction kettle, stirring at room temperature for 0.3-0.5 hours, then cooling to 30°C, adding a physical foaming agent, and stirring to obtain component A; mixing component A and component B for 8 seconds, pouring them into a mold, foaming and curing for 12 hours, and then opening the mold to obtain the polyurethane and graphene composite methane adsorption material.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] The present invention integrates graphene-modified isocyanate into the polyurethane system, which not only greatly improves the methane adsorption capacity of the material, but also significantly enhances the mechanical properties of the composite material due to the high strength and high toughness of graphene, making it more durable. In addition, the preparation method is simple and efficient, the raw materials are easily available and the cost is controllable, which ensures that the composite material has good processing performance and can flexibly meet the needs of diversified products. The prepared polyurethane and graphene composite methane adsorption material shows broad application potential in many fields such as natural gas extraction, storage and transportation, and chemical production. DETAILED DESCRIPTION
[0035] The present invention is further described below with reference to the embodiments, but they do not limit the implementation of the present invention.
[0036] The raw materials used in the examples and comparative examples are conventional commercially available raw materials unless otherwise specified, and the process methods used in the examples and comparative examples are conventional methods in the art unless otherwise specified.
[0037] Example 1
[0038] The polyurethane and graphene composite methane adsorption material is prepared by reacting component A and component B in a mass ratio of 1:1;
[0039] Wherein, the A component is composed of the following raw materials in parts by weight:
[0040] R5118G: 60 parts;
[0041] R6205: 30 servings;
[0042] R403: 5 parts;
[0043] 4400T: 5 copies;
[0044] Water: 2.5 parts;
[0045] H3565: 2 copies;
[0046] UR5931: 2 copies;
[0047] PC-5: 0.6 parts;
[0048] PC-8: 5.3 parts;
[0049] BDMA: 2.1 parts;
[0050] PC-41: 0.8 parts;
[0051] TMR-2: 0.5 parts;
[0052] n-Pentane: 13 parts;
[0053] The B component is graphene-modified isocyanate;
[0054] The preparation method of the graphene-modified isocyanate is as follows: adding graphene with a particle size of 25±15 μm to N,N-dimethylformamide, wherein the mass ratio of graphene to N,N-dimethylformamide is 1:50, then adding polyvinyl pyrrolidone, wherein the amount of polyvinyl pyrrolidone added is 0.5wt.% of the total amount of graphene, and ultrasonicating for 30 minutes to obtain a graphene dispersion; adding dibutyltin dilaurate to the graphene dispersion heated to 80°C, and then adding PM200, heating and stirring to react for 5 hours, and filtering after the reaction is completed to obtain the graphene-modified isocyanate, wherein the amount of dibutyltin dilaurate added is 0.5wt.% of the total amount of PM200, and the amount of graphene added is 1wt.% of the total amount of isocyanate.
[0055] The preparation method of the polyurethane and graphene composite methane adsorption material is as follows: R5118G, R6205, R403, 4400T, H3565, UR5931, PC-5, PC-8, BDMA, PC-41, TMR-2 water are put into a reaction kettle, stirred at room temperature for 0.5 hours, then cooled to 30°C, and then n-pentane is added to the stirring kettle, and component A is obtained after stirring; component A and component B are mixed and stirred for 8 seconds, then poured into a mold, foamed and cured for 12 hours, and then the mold is opened to obtain the polyurethane and graphene composite methane adsorption material.
[0056] Example 2
[0057] The polyurethane and graphene composite methane adsorption material is prepared by reacting component A and component B in a mass ratio of 1:1.1;
[0058] Wherein, the A component is composed of the following raw materials in parts by weight:
[0059] R5118G: 50 copies;
[0060] R6205: 30 servings;
[0061] R403: 10 parts;
[0062] 4400T: 10 copies;
[0063] Water: 2.5 parts;
[0064] H3565: 2 copies;
[0065] UR5931: 2 copies;
[0066] PC-5: 0.3 parts;
[0067] PC-8: 6.8 parts;
[0068] BDMA: 2.1 parts;
[0069] PC-41: 1.8 parts;
[0070] TMR-2: 0.5 parts;
[0071] n-Pentane: 14 parts;
[0072] The B component is graphene-modified isocyanate;
[0073] The preparation method of the graphene-modified isocyanate is as follows: adding graphene with a particle size of 25±15 μm to N,N-dimethylformamide, wherein the mass ratio of graphene to N,N-dimethylformamide is 1:100, then adding polyvinyl pyrrolidone, wherein the amount of polyvinyl pyrrolidone added is 0.3wt.% of the total amount of graphene, and ultrasonicating for 30 minutes to obtain a graphene dispersion; adding dibutyltin dilaurate to the graphene dispersion heated to 80°C, and then adding PM200, heating and stirring to react for 5 hours, and filtering after the reaction is completed to obtain the graphene-modified isocyanate, wherein the amount of dibutyltin dilaurate added is 0.4wt.% of the total amount of PM200, and the amount of graphene added is 3wt.% of the total amount of isocyanate.
[0074] The preparation method of the polyurethane and graphene composite methane adsorption material is the same as that in Example 1.
[0075] Example 3
[0076] The polyurethane and graphene composite methane adsorption material is prepared by reacting component A and component B in a mass ratio of 1:1.2;
[0077] Wherein, the A component is composed of the following raw materials in parts by weight:
[0078] R5118G: 50 copies;
[0079] R6205: 40 copies;
[0080] R403: 5 parts;
[0081] 4400T: 5 copies;
[0082] Water: 2.5 parts;
[0083] H3565: 2 copies;
[0084] UR5931: 2 copies;
[0085] PC-5: 0.5 parts;
[0086] PC-8: 6 parts;
[0087] BDMA: 2.5 parts;
[0088] PC-41: 2 parts;
[0089] TMR-2: 0.5 parts;
[0090] n-Pentane: 16 parts;
[0091] The B component is graphene-modified isocyanate;
[0092] The preparation method of the graphene-modified isocyanate is as follows: adding graphene with a particle size of 25±15 μm to N,N-dimethylformamide, wherein the mass ratio of graphene to N,N-dimethylformamide is 1:80, then adding polyvinyl pyrrolidone, wherein the amount of polyvinyl pyrrolidone added is 0.4wt.% of the total amount of graphene, and ultrasonicating for 30 minutes to obtain a graphene dispersion; adding dibutyltin dilaurate to the graphene dispersion heated to 80°C, and then adding PM200, heating and stirring to react for 5 hours, and filtering after the reaction is completed to obtain the graphene-modified isocyanate, wherein the amount of dibutyltin dilaurate added is 0.3wt.% of the total amount of PM200, and the amount of graphene added is 2wt.% of the total amount of isocyanate.
[0093] The preparation method of the polyurethane and graphene composite methane adsorption material is the same as that in Example 1.
[0094] Comparative Example 1
[0095] The difference from Example 1 is that component A further includes 25 parts by weight of graphene (particle size is 25±15 μm), and component B is PM200;
[0096] The preparation method of the polyurethane material is as follows: R5118G, R6205, R403, 4400T, H3565, UR5931, PC-5, PC-8, BDMA, PC-41, TMR-2, water and graphene are put into a reaction kettle, stirred at room temperature for 0.5 hours, then cooled to 30°C, and then n-pentane is added to the stirring kettle, and component A is obtained after stirring; component A and component B are mixed and stirred for 8 seconds, then poured into a mold, foamed and cured for 12 hours, and then the mold is opened to obtain the polyurethane material.
[0097] The polyurethane materials prepared in Examples 1 to 3 and Comparative Example 1 were subjected to performance tests, and the test methods were as follows:
[0098] Core density (kg / m 3 ): Tested in accordance with GB / T 6343-2009;
[0099] Compression strength (kPa): Tested in accordance with GB / T 8813-2020;
[0100] Opening rate (%): Tested in accordance with GB / T 10799-2008;
[0101] Dimensional change rate (%): Tested in accordance with GB / T 8811-2008, test conditions: 120°C, 24h;
[0102] Methane adsorption (wt.%): tested in accordance with GB / T 21650.3-2011.
[0103] The test results are shown in Table 1.
[0104] Table 1 Performance test results
[0105] project Core density Compression strength Opening rate Dimensional change rate Methane adsorption Example 1 24.3 270 97 <0.1 55.6 Example 2 25.2 289 95 <0.1 57.32 Example 3 24.8 278 98 <0.1 56.85 Comparative Example 1 22.1 227 95 <0.1 50.58
[0106] It can be seen from the data in Table 1 that the polyurethane materials obtained in Examples 1-3 have higher compressive strength and smaller dimensional change rate, ensuring that the foam has good mechanical properties, can resist external forces and is not easily deformed, and good flow properties ensure its filling degree in different environments and molds. The open porosity is high, providing a large number of gas adsorption sites. At the same time, the strong methane adsorption capacity of graphene ensures a higher methane adsorption amount.
[0107] In Comparative Example 1, since unmodified graphene is directly added to the polyurethane material, the core density, compression strength and open porosity of the obtained polyurethane material decrease, and the methane adsorption amount is low.
Claims
1. A polyurethane and graphene composite methane adsorption material, characterized in that: It includes component A and component B in a mass ratio of 1:(1-1.2); The A component includes the following raw materials in parts by weight: Polyether polyol A: 50-60 parts; Polyether polyol B: 30-40 parts; Polyether polyol C: 5-10 parts; Polyether polyol D: 5-10 parts; Foam stabilizer: 3-5 parts; Physical foaming agent: 13-16 parts; Chemical foaming agent: 2-3 parts; Composite catalyst: 9-12 parts; The B component is graphene-modified isocyanate; The functionality of the polyether polyol A is 4-6, and the hydroxyl value is 360-400 mgKOH / g; The functionality of the polyether polyol B is 3.8-4.2, and the hydroxyl value is 360-400 mgKOH / g; The functionality of the polyether polyol C is 4, and the hydroxyl value is 745-775 mgKOH / g; The functionality of the polyether polyol D is 4, and the hydroxyl value is 350-380 mgKOH / g; The preparation method of the graphene-modified isocyanate is as follows: adding graphene to N,N-dimethylformamide, then adding polyvinyl pyrrolidone, and ultrasonically obtaining a graphene dispersion; adding isocyanate and a tin catalyst to the graphene dispersion, heating the reaction, and obtaining the graphene-modified isocyanate.
2. The polyurethane and graphene composite methane adsorption material according to claim 1, characterized in that: The viscosity of the polyether polyol A at 25°C is 6000-9000 mPa·s; the viscosity of the polyether polyol B at 25°C is 2000-3000 mPa·s; the viscosity of the polyether polyol C at 50°C is 1400-2400 mPa·s; and the viscosity of the polyether polyol D at 25°C is 8000-12000 mPa·s.
3. The polyurethane and graphene composite methane adsorption material according to claim 1, characterized in that: In the preparation method of the graphene-modified isocyanate, the isocyanate is polymethylene polyphenyl polyisocyanate, the tin catalyst is dibutyltin dilaurate; the amount of graphene added is 1-3wt.% of the total amount of isocyanate, the mass ratio of graphene to N,N-dimethylformamide is 1:(50-100), the amount of polyvinyl pyrrolidone added is 0.1-0.5wt.% of the total amount of graphene, and the amount of tin catalyst added is 0.1-0.5wt.% of the total amount of isocyanate.
4. The polyurethane and graphene composite methane adsorption material according to claim 1, characterized in that: The foam stabilizer is silicone oil.
5. The polyurethane and graphene composite methane adsorption material according to claim 1, characterized in that: The physical foaming agent is pentane.
6. The polyurethane and graphene composite methane adsorption material according to claim 1, characterized in that: The chemical foaming agent is water.
7. The polyurethane and graphene composite methane adsorption material according to claim 1, characterized in that: The composite catalyst is a composite catalyst of PC-5, PC-8, BDMA, PC-41 and TMR-2, and the mass ratio thereof is (0.3-0.6):(5-7):(2-3):(0.5-2):0.
5.
8. The polyurethane and graphene composite methane adsorption material according to claim 1, characterized in that: The polyether polyols A, B, C and D are R5118G, R6205, R403 and 4400T respectively.
9. The polyurethane and graphene composite methane adsorption material according to claim 1, characterized in that: The particle size of the graphene is 10-40 μm.
10. A method for preparing the polyurethane and graphene composite methane adsorption material according to claims 1-9, characterized in that: The method comprises the following steps: putting polyether polyol A, polyether polyol B, polyether polyol C, polyether polyol D, a foam stabilizer, a composite catalyst and a chemical foaming agent into a reaction kettle, stirring at room temperature for 0.3-0.5h, then cooling, adding a physical foaming agent, and stirring to obtain component A; mixing component A and component B, and then pouring the mixture into a mold, foaming, curing, and opening the mold to obtain a polyurethane and graphene composite methane adsorption material.
Citation Information
Cited By
Multifunctional polyurethane thermal insulation material for fish tank and preparation method of multifunctional polyurethane thermal insulation material
CN121343113A